Force/Torque Sensorless Impedance Control for Indirect Driven Robot-Aided Gait Rehabilitation System - Quoc Van Tran; Kim, Sehun; Ryu, Jeha; Kang, Sungchul; Lee, Kyunghwan (2015 IEEE/ASME INTERNATIONAL CONFERENCE ON ADVANCED INTELLIGENT MECHATRONICS (AIM), 2015)
Robot gait rehabilitation has been emerging as an important training technique for patients whose ability to walk is impaired. The "patient-cooperative" approaches are able to detect patient's voluntary efforts and allow patients to actively influence a gait pattern during rehabilitation processes. The impedance control method is a key technique of "patient-cooperative" strategies that allows deviating desired trajectories by sensing interaction torque. This paper introduces an indirect drive gait training rehabilitation robot system which composed of timing belt and harmonic drive transmissions. We present compensation methods and investigate reaction torque observer (ROB) for estimating patient/robot interaction torque and its application in force/torque sensorless impedance control of patient-cooperative strategy in gait rehabilitation.